Review of the book The Theory of Peasant Co-operatives by Alexander Chayanov: A Teoria das Cooperativas Camponesas de Alexander Chayanov - Deggerone, Zenicleia Angelita (Programa de Pós-graduação em Desenvolvimento, Agricultura e Sociedade da Universidade Federal Rural do Rio de Janeiro (CPDA/UFRRJ), 2018)
Review of the book The Theory of Peasant Co-operatives by Alexander Chayanov.Keywords: Alexander Chayanov; peasant co-operatives.CHAYANOV, Alexander. A Teoria das Cooperativas Camponesas de Alexander Chayanov. Porto Alegre: Editora UFRGS, 2017, 296 p. Resenha de: DEGGERONE, Zenicleia Angelita. A Teoria das Cooperativas Camponesas de Alexander Chayanov. Estudos Sociedade e Agricultura, v. 26, n. 3, p. 701-705, out. 2018.Submitted in june 2018.Accepted in july 2018.